2019
DOI: 10.1126/sciimmunol.aax4453
|View full text |Cite
|
Sign up to set email alerts
|

Lin28b controls a neonatal to adult switch in B cell positive selection

Abstract: The ability of B-1 cells to become positively selected into the mature B cell pool, despite being weakly self-reactive, has puzzled the field since its initial discovery. Here, we explore changes in B cell positive selection as a function of developmental time by exploiting a link between CD5 surface levels and the natural occurrence of self-reactive B cell receptors (BCRs) in BCR wild-type mice. We show that the heterochronic RNA binding protein Lin28b potentiates a neonatal mode of B cell selection character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 85 publications
4
41
0
Order By: Relevance
“…Since then, additional evidence from the lymphoid, erythroid, and megakaryocyte lineages has cemented the role of Lin28b as a molecular master switch for fetal hematopoiesis 28‐32 . In a recent study, we explored changes in B cell positive selection as a function of developmental timing 33 . Like in T cells, 34 we show that CD5 levels directly correlate with self‐reactivity in the mature B cell repertoire.…”
Section: A Molecular Switch Relaxes the Tolerance Threshold Early In mentioning
confidence: 84%
See 3 more Smart Citations
“…Since then, additional evidence from the lymphoid, erythroid, and megakaryocyte lineages has cemented the role of Lin28b as a molecular master switch for fetal hematopoiesis 28‐32 . In a recent study, we explored changes in B cell positive selection as a function of developmental timing 33 . Like in T cells, 34 we show that CD5 levels directly correlate with self‐reactivity in the mature B cell repertoire.…”
Section: A Molecular Switch Relaxes the Tolerance Threshold Early In mentioning
confidence: 84%
“…Interestingly, ectopic Lin28b in the adult was not sufficient to recapitulate the clonal dominance of the canonical VH11 and VH12 encoded PtC reactive public clonotypes. 32,33 Instead, B-1 cells licensed by Lin28b exhibit N-rich junctional diversity similar to that seen in the adult B cell repertoire. These results are in line with the fact that fetal lymphopoiesis takes place in the absence of terminal deoxynucleotidyl transferase (TdT) expression responsible for N nucleotide additions 36,37…”
Section: A Molecul Ar Switch Rel a Xe S The Toler An Ce Thre S Holdmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it was recently shown that antigen receptor specificity is sufficient to induce cell proliferation and acquisition of the B-1 phenotype and function (Graf et al, 2019). Lin28b, a regulator of fetal hematopoiesis, is important in the generation of B1a lineage, and loss of its expression controls the switch from neonatal to adult B cell production (Vanhee et al, 2019). Low levels of IL-7, a cytokine crucial for adult B cell development, in FL favors the generation of B1, highlighting the impact of the microenvironment on the preferential production of particular cell types (Wong et al, 2019).…”
Section: B Cell Developmentmentioning
confidence: 99%